Dynamics of Human Resource Management: Integrating Technology, Sustainability, and Adaptability in the Modern Organizational Landscape - Nurimansjah, Ris Akril (Golden Ratio of Mapping Idea and Literature Format, 2023)
This research explores the dynamics of Human Resource Management (HRM) in facing the challenges of the contemporary era characterized by technological integration, environmental sustainability, and organizational adaptability. Through a review of scholarly articles, this research explores the relationship between innovative HRM practices and their impact on organizational performance, employees, and response to change. Technology integration in HRM is a focus of attention. The integration of Artificial Intelligence (AI) and Advanced Analytics is changing the paradigm of HRM processes by improving efficiency, decision-making, and employee experience. The review showed that technology enables personalization of HRM and has a positive impact on organizational performance. The importance of environmental sustainability is also reflected in the practice of Green Human Resource Management (GHRM). The integration of environmentally sound transformational leadership components, environmentally sound social capital, and environmentally sound values in GHRM has a positive correlation with pro-environmental behavior in the workplace. These findings encourage a sustainable organizational culture and support employee performance. The era of the Fourth Industrial Revolution (Industry 4.0) presents new challenges for HRM. The integration of advanced technologies shapes organizational dynamics and employee behavior. This research highlights the importance of adaptability in HRM to deal with rapid contextual changes. Supply chain resilience is becoming an important aspect of HRM, especially in the face of unexpected disruptions. HRM practices that encourage employee participation in supply chain resilience development have a positive impact on organizational resilience and operational performance. The COVID-19 pandemic crisis demands adaptive and innovative HRM practices. This research shows that adaptable HRM practices contribute to organizational readiness in the face of challenges and sudden changes. The results of this review provide a foundation for further research in understanding the relationship between HRM practices and organizational and employee performance. In-depth quantitative research is expected to test the hypotheses formulated and provide guidance for effective HRM strategies in the face of modern organizational dynamics.